2009
DOI: 10.1111/j.1468-2389.2009.00475.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance‐Appraisal Beliefs of Chinese Employees in Hong Kong and the Pearl River Delta

Abstract: Working adults from Hong Kong (HK; N ¼ 102) and the Pearl River Delta (PRD; N ¼ 96) participated in a Chinese-language, 20-item, structured interview. The interview addressed five topics: performance criteria, implementation of the appraisal, factors attributed to performance, methods of feedback, and concerns about the use of performance appraisal (PA) at work. Results indicated that most respondents believe that PA facilitates communication between superiors and subordinates, that effective performance is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Lunnan et al (2005) suggested that when transferring “foreign best practices” to MNC subsidiaries, national values may present some initial barriers. In line with those views, a recent study by Cheng and Cascio (2009) suggested that there were obvious differences in the preference for appraisal practices between employees in China and Western countries. However, in spite of such awareness, it is somewhat surprising to find that standardized performance appraisal systems are still commonly applied in many MNCs as a convenient way of comparing performance across company boundaries (Dowling et al , 1999; Lindholm et al , 1999).…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations
“…Lunnan et al (2005) suggested that when transferring “foreign best practices” to MNC subsidiaries, national values may present some initial barriers. In line with those views, a recent study by Cheng and Cascio (2009) suggested that there were obvious differences in the preference for appraisal practices between employees in China and Western countries. However, in spite of such awareness, it is somewhat surprising to find that standardized performance appraisal systems are still commonly applied in many MNCs as a convenient way of comparing performance across company boundaries (Dowling et al , 1999; Lindholm et al , 1999).…”
Section: Introductionmentioning
confidence: 71%
“…This finding is to some extent consistent with a conclusion in the research of Lindholm et al (1999), who noted “the seeming lack of initiative” of local Chinese employees in the workplace and suggested that without clear instructions, Chinese employees tended to avoid the responsibility to do such tasks even though they may have already noticed it. Similarly, Cheng and Cascio (2009) stated that in high uncertain‐avoidance cultures likely China, employees usually expected supervisors to provide clear instructions because they were commonly assumed to be “the one with knowledge”. Another explanation of this lack of responsibility may have a root in a top‐down hierarchical organizational structure, as suggested by Hempel (2001) that obedience is one of the important performance dimensions in the context of China.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various explanations have been offered. For example, a cross-cultural perspective in individualism-collectivism (Farh et al, 1991; Xie et al, 2006; Heine and Hamamura, 2007; Cheng and Cascio, 2009; Ng et al, 2011) was found to be relevant in rating biases. Recently, there had been evidence supporting the contrary (Brown, 2010)—that is, while cultural factors may moderate leniency effect, the tendency to self-enhance is universal.…”
Section: Introductionmentioning
confidence: 99%
“…These practices stand in contrast to more typical performance appraisal practices of Western MNEs that are generally higher on individualism and lower on power distance. Western practices tend to involve multiple contributors to the appraisal process (Cheng & Cascio, 2009; Fletcher & Perry, 2001), as well as performance criteria being objective and quantitative (Giangreco et al, 2010) to meet expectancy principles that people will be rewarded directly for their performance (Kudisch, Fortunato, & Smith, 2006).…”
Section: A Culture‐bound Practicementioning
confidence: 99%